Training Systems Management Implications. - Desai, Mayur S.; Richards, Thomas; Eddy, John Paul (College Student Journal)
The rate of growth of technology is accelerating. This has caused a major issue of training end users to keep up with the growing technology. As a result, training managers are challenged to find effective and innovative ways to train end users. Corporations are investing large sum of money in training end users with expectations that end users will continue to be productive. More specifically corporate executives are concerned about long-term effect of training on end user productivity. This paper presents a training model and strategies corporations could adopt to effectively train their employees. The study reports the findings of longitudinal study conducted in a field setting. The study discusses management implications for training managers.